Ray Cox Memorial: inter-departmental correspondence (copy) - Bolton, W. J.
041-0029-001 W. J. BOLTON Mr. E. PARKIN International April 14, 1937 RAY COX MEMORIAL Will you please earmark the £20 received yesterday from Mr. Witt (Southampton) for the Ray Cox Memorial. A cheque for £40 is to be sent to Schevenels today. This item should be specified thus on the expenditure side of the next statement of accounts. Mr. Witt will be sending another £25 shortly, and the balance later, so as to make up £60 or the cost of the apparatus to be purchased as the Memorial. The exact amount we shall get to know later from the I.F.T.U. WJB/AC/615. 292/946/41/29